Al-Kindy College Medical Journal: An Audit of Publications for One Decade (2015-2024) - Al-Mendalawi, Mahmood D.; Al-Edanni, Mohammed Shihab (AL-Kindy College Medical Journal, 2025)
The Al-Kindy College Medical Journal (KCMJ) is an Iraqi scholarly journal published by the Al-Kindy College of Medicine, University of Baghdad. It was officially founded in 2004. It is a peer-reviewed journal, published in both online and printed forms. It has a mission to offer a publication platform that mirrors recent knowledge and findings in the field of medicine and medical sciences. It publishes various types of articles, including editorial, review article, research article, brief report, case report, and letter to editor. It accepts articles in the English language. It was biannually published till 2021 when it started to launch three issues per year. The journal is registered with numerous partners, including Iraqi Academic Scientific Journals (IASJ), CrossRef, Google Scholar, Researchgate, Scopus, Open Access Scholarly Publishing Association (OASPA), Committee on Publication Ethics (COPE), Directory of Open Access Journals (DOAJ), and Digital Object Identifier (DOI) System. The journal is archived by Clockss and Repository of the University of Baghdad. All articles published in the journal are freely available for everyone to read and access. Globally, a publication audit is usually exercised as it is regarded as an indispensable tool to evaluate the scientific progress of a particular academic journal in terms of achieving higher quality, attaining wider visibility, attracting more or better researchers/authors, getting recognition, expanding journal's dissemination,  increasing the number of subscriptions, and planning for the future development.